(untitled) (Filološke pripombe, 2021)
The theoretical descriptions of postmodernist fiction, offered by Brian McHale, Patricia Waugh, Dubravka Oraic Tolic, emphasize the ontological dominant that is embodied in the literary texts as a problematization of the boundaries between worlds and texts. This paper will elaborate thеse theoretical premises through the interpretation of the novel The Мathematician’s Daughter by the Macedonian author Venko Andonovski. The interpretive focus will be on three levels. 1. the interpretation of ontological themes in the novel; 2.interpretation of metafictional devices (intertextuality, intartextuality, transtextuality, vacant quotation, recursive structures, transworld identities), through which these themes are articulated in the novel; 3. the interpretation of the function that these metafictional devices have in demonstration of ontological games with the boundaries between worlds (literature - reality, art - life, fact - fiction, author-character) and between texts (original and plagiarized, texts and metatexts). The interpretation of Venko Andonovski’s novel led to two conclusions with theoretical implications. First, all devices in the novel participate in the affirmation of the complex metafictional theme (the reality-fiction relationship) and, in that sense, participate in redefining the understanding of the novel as a mimetic genre. Second: the ontological games that participate in the novel’s structure spill over into the act of reception of the text, also involving the reader in ontological games.